A singular remedy: cinchona across the Atlantic World, 1751-1820 - Gänger, Stefanie (Cambridge University Press, 2021)
"Stefanie Gänger explores how medical knowledge was shared across societies tied to the Atlantic World between 1751 and 1820. Centred on Peruvian bark or cinchona, Gänger shows how that remedy and knowledge about its consumption - formulae for bittersweet, 'aromatic' wines, narratives about its discovery or beliefs in its ability to prevent fevers - were understood by men and women in varied contexts. These included Peruvian academies and Scottish households, Louisiana plantations and Moroccan court pharmacies alike. This study in plant trade, therapeutic exchange, and epistemic brokerage shows how knowledge weaves itself into the fabric of everyday medical practice in different places"--
Includes bibliographical references and index
Keywords: Geschichte 1751-1820; Pharmazie; Chinarindenbaum